1989
DOI: 10.1088/0022-3727/22/1/027
|View full text |Cite
|
Sign up to set email alerts
|

The study of a ferrofluid exhibiting both Brownian and Neel relaxation

Abstract: The low-field complex susceptibility curves of ferrofluids have in general a Debye-type profile with a loss component which peaks at a frequency from which it is possible to estimate the average relaxation time of the particles in the ferrofluid. The authors report on magnetic measurements on a water-based ferrofluid whose loss curve displayed two distinct peaks. It is concluded that one peak is due to Brownian relaxation and the other is due to a combination of Brownian and Neel relaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 9 publications
1
66
0
Order By: Relevance
“…Refs. [11][12][13]). For instance, Bacri et al [13] measured magneto-optical relaxation in order to determine elastic moduli of gel near the sol-gel transition.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%
“…Refs. [11][12][13]). For instance, Bacri et al [13] measured magneto-optical relaxation in order to determine elastic moduli of gel near the sol-gel transition.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%
“…(1). Fannin [20] has assessed the theoretical contribution of the Néel relaxation by weight-averaging the susceptibilities with particle radii distributions obtained from electron microscopy. In the present study, we integrate Eq.…”
Section: Resultsmentioning
confidence: 99%
“…For the particle sizes used in this study, Néel relaxation would be observed in the MHz-GHz region [7]; thus in the frequency range measured here Néel relaxation is considered to be dominant.…”
Section: Introductionmentioning
confidence: 92%